QARDH DAN IJARAH PADA GADAI EMAS - Sutarti, Sutarti; Kristanto, Eri; Andriyani, Melinda (JURNAL EKONOMI, 2024)
This Study was conducted with the aim of knowing the suitability of the Implementation of the Qardh and Ijarah contracts on gold pawn transactions at Bank Syariah Indonesia Cilacap Branch Office with indicators of Fatwa of DSN MUI No. 19/DSN-MUI/IV/2001 and Fatwa of DSN MUI No. 112/DSN-MUI/IX/2017. This Research method users descriptive qualitative methods by collecting data byobservation and interviews. The Result of this study indicate that the implementation of Qardh and Ijarah on gold pawn transactions at Bank Syariah Indonesia Cilacap Branch Office is in accordance with the Fatwa of DSN MUI No. 19/DSN-MUI/IV/2001 and Fatwa DSN MUI No. 112/DSN-MUI/IX/2017